On Defining Translation - García-Landa, Mariano (Meta, 2006)
AbstractIn Volume 50, no 4, December 2005, Maria Tymoczko traces some “Trajectories of Research in Translation Studies” and the first trajectory consisting in the difficulties even impossibility of defining translation. I try to show here that it is perfectly possible to define translation if you look at it, not from the viewpoint of “Translations Studies” aka Traductologie, but from the viewpoint of philosophy.